2004
DOI: 10.1038/sj.bjc.6601771
|View full text |Cite
|
Sign up to set email alerts
|

Targeted radiotherapy of brain tumours

Abstract: The utility of external beam radiotherapy for the treatment of malignant brain tumours is compromised by the need to avoid excessive radiation damage to normal CNS tissues. This review describes the current status of targeted radiotherapy, an alternative strategy for brain tumour treatment that offers the exciting prospect of increasing the specificity of tumour cell irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…[8][9][10] As Nimotuzumab is an IGg1 humanized mAb, it could activate more efficiently immune effector cells in the tumor area than murine mAbs. 42 The visual inspection of the processed scintigraphic images and the biodistribution calculations revealed that 188 Re-Nimotuzumab was retained in tumour cavity and adjacent malignant tissues for a long period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] As Nimotuzumab is an IGg1 humanized mAb, it could activate more efficiently immune effector cells in the tumor area than murine mAbs. 42 The visual inspection of the processed scintigraphic images and the biodistribution calculations revealed that 188 Re-Nimotuzumab was retained in tumour cavity and adjacent malignant tissues for a long period.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] The infusion of radiolabelled monoclonal antibodies directly into the postsurgical resection cavity has enabled the delivery of high radiation doses to the affected area without important harm to the surrounding normal brain tissue or distant organs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this high linear energy transfer (LET), a-emitters induce cell death with only few nuclear hits to the target cell. There have been numerous pre-clinical studies conducted using RIT involving a-emitters, but so far only clinical studies involving acute myeloid leukemia and glioblastoma patients have been reported [20].…”
Section: Replacing 2 Gy Tbi With Rit In a Non-myeloablative Regimen Fmentioning
confidence: 99%
“…It is beyond the scope of this review to discuss all published studies. For a detailed review on RIT, see Zalutsky, 111 Carlsson et al, 110 Seidl 114 and Dietrich 115 . Table 1 summarizes the studies reviewed here.…”
Section: Particle Therapymentioning
confidence: 99%
“…By contrast, 131 I is a medium-energy b (range 0.9 mm) and g radiation emitter that significantly contributes to the whole-brain radiation dose. 110 Clinical experience with radioimmunotherapy The majority of RIT studies in gliomas are performed with antitenascin-C or antiEGFR mAb. The expression of tenascin and of EGFR increases with advancing brain tumour grade with .90% of GBM biopsies exhibiting tenascin overexpression, 111 while EGFR overexpression varies between 31% and 95% in patients with GBM.…”
Section: Particle Therapymentioning
confidence: 99%